First report of leaf blight caused by Apoharknessia eucalyptorum on Eucalyptus grandis × Eucalyptus urophylla in China - Liao, Wangjiao (Plant disease, 2022)
Eucalypt GL-9 (Eucalyptus grandis × Eucalyptus urophylla) is one of the most widely grown genotypes of Eucalyptus in China. Each year, leaf blight causes serious economic losses in the eucalyptus industry in the south of China. In December 2019, a leaf blight disease was found to be widespread on eucalyptus GL-9 in Hechi in Guangxi, China (25°22'17"N, 108°15'32"E). Symptomatic lesions were usually brown at the early stage of infection and then turned off-white at the late stage. They had a large number of black round pycnidia randomly dispersed on the surface. Most of the lesions initially started from the leaf tip and then gradually expanded to the base of the leaf. Three randomly sampled leaves were washed using sterile water. Next, small pieces of tissue (5×10 mm) were removed from the margins of the lesions, surface disinfected with 75% ethanol for 1 min and 0.1% HgCl2 for 3 min, and then washed three times with sterile water. The tissues were placed on potato dextrose agar (PDA) and incubated at 28°C for 5 days to observe the fungus morphological characteristics. The hyphae on the PDA were milky yellow, and the PDA was light yellow when viewed from the bottom, with few aerial hyphae. The colonies had petal-like edges. In the later stage, hyphae in the center of the colonies turned brown. Three representative isolate (EC7, EC8, EC10) were selected for further study. Their conidia were olive-shaped, spindle-shaped, or obliquely globose, 8.80-11.93 μm in length (10.35 μm in average), 4.69-7.33 μm in width (6.06 μm in average) (n=100 in each isolate), with a conical apiculus and a hyaline basal appendage that was tubular, smooth, and thin-walled. For molecular identification, their genomic DNA was extracted using a Genomic DNA Kit (Tiangen, China). The internal transcribed spacer (ITS) region of rDNA and β-tubulin (TUB) genes were amplified using ITS5/ITS4 and βt2a/βt2b primer sets, respectively (White et al. 1990). BLASTn searches showed that the ITS and TUB sequences had the highest identity with Apoharknessia eucalyptorum strains, with 100% (586/586 in EC7 and EC8, 590/590 in EC10) identity for ITS (KY979752.1) and 99% (502/505 in EC7, 506/508 in EC8 and 504/507 in EC10) identity for TUB (KY979919.1) of ex-type CBS 142519. The ITS and TUB sequences of three isolates were submitted to GenBank (EC7: OM060439 and OM103586, EC8: OM679378 and OM715153, EC10: OM679377 and OM715152). A maximum likelihood phylogenetic tree was constructed by combining the two sequenced loci in MEGA7. Three isolates clustered in the A. eucalyptorum clade with 92% bootstrap support. Thus, based on morphological (Crous et al. 2017; Garrett et al. 2018) and molecular characteristics, the pathogen was identified as A. eucalyptorum. In a pathogenicity test, twenty healthy GL-9 seedlings were collected, and were divided into four groups. Seedlings from groups 1-3 were used to inoculate three isolates respectively, and seedlings from another group were sprayed distilled water as control. Before test, leaves were washed with sterile water, surface disinfected with 75% ethanol, and then rinsed with sterile water. After drying, an inoculation needle was used to make tiny wounds near the leaf margin on each leaf. Next, conidia solution (1×107 conidia/ml) and sterile water were sprayed to leaves in different groups and moistened with airtight bags. After 3 days, airtight bags were moved. Lesions appeared on all the pathogen-inoculated leaves, whereas only the inoculation point turned brown on the control leaves. The pathogenicity test was repeated three times and the same results were obtained. Fungi were re-isolated from symptomatic leaves and identified as A. eucalyptorum following the same methodologies used for the initial identification. To our knowledge, this is the first report of A. eucalyptorum causing leaf blight on E. grandis × E. urophylla in China. This study expands the understanding of the pathogen of leaf blight on E. grandis × E. urophylla. More research is needed to develop effective strategies to manage this disease